2012
DOI: 10.2527/jas.2012-5078
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sulfur concentration affects rumen hydrogen sulfide concentrations in feedlot steers during transition and finishing

Abstract: Angus steers (n = 96; 321 ± 29 kg BW) were used to determine how previous exposure to increased dietary S would affect ruminal hydrogen sulfide concentrations ([H(2)S]) in the feedlot, to investigate the effects of dietary S on ruminal [H(2)S] during transition and finishing, and to determine if dietary S affects the glutathione status of finishing cattle. Steers were strip-grazed on smooth bromegrass (Bromus inermis L.) over a 35 d period and received a dry distillers grains plus solubles (DDGS) supplement at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…Loneragan et al (2005) utilized three concentrations of sulfate in the drinking water (136, 583, 2,360 mg sulfate/L) of feedlot cattle and observed that ruminal H 2 S concentrations peaked on d 31 of the study, after which concentrations decreased and stabilized for the remainder of the trial. Drewnoski et al (2012b) found that cattle consuming a high S diet had concentrations of H 2 S that increased relative to their S intake during the first 30 d on a finishing diet, regardless of whether or not cattle were previously exposed to increased dietary S while on a high roughage diet. Delfiol et al (2013) recently reported that in sheep fed 0.9 or 1.2% S (in diets containing 31% oat hulls and 5% bermudagrass hay) rumen H 2 S concentrations reached a peak approximately 5 to 7 wk into the finishing period.…”
Section: Adaptation To Finishing Dietsmentioning
confidence: 93%
See 1 more Smart Citation
“…Loneragan et al (2005) utilized three concentrations of sulfate in the drinking water (136, 583, 2,360 mg sulfate/L) of feedlot cattle and observed that ruminal H 2 S concentrations peaked on d 31 of the study, after which concentrations decreased and stabilized for the remainder of the trial. Drewnoski et al (2012b) found that cattle consuming a high S diet had concentrations of H 2 S that increased relative to their S intake during the first 30 d on a finishing diet, regardless of whether or not cattle were previously exposed to increased dietary S while on a high roughage diet. Delfiol et al (2013) recently reported that in sheep fed 0.9 or 1.2% S (in diets containing 31% oat hulls and 5% bermudagrass hay) rumen H 2 S concentrations reached a peak approximately 5 to 7 wk into the finishing period.…”
Section: Adaptation To Finishing Dietsmentioning
confidence: 93%
“…In this study, 3 or the 4 steers consuming a high S diet exhibited signs of PEM. However, many studies have observed concentrations of H 2 S two to three fold greater than 2,000 mg/L without observing clinical signs of PEM (Neville et al, 2010;Drewnoski et al, 2012b;Morine et al, 2012b;Drewnoski and Hansen, 2013a).…”
Section: Proposed Mechanisms Of Cellular Toxicity Due To Hydrogen Sulmentioning
confidence: 99%
“…Each fistula was equipped with a small polyvinyl chloride (PVC) fitting (1.27 cm LASCO PVC I; LASCO Fittings, Inc., Brownsville, TN) kept capped to minimize gas loss, as described by Drewnoski et al (2012a). To measure H 2 S concentration of the ruminal gas, a metal rod 45.72 cm long was inserted through the PVC fitting with a short piece of tubing connecting the rod to the gas detector tube and volumetric gas sampling pump (Matheson-Kitagawa 8014-400B; Matheson-Kitagawa, Kitigawa, Japan) according to the procedure described by Drewnoski et al (2012b).…”
Section: Sample Collection and Analytical Proceduresmentioning
confidence: 99%
“…the effect would not appear until the product accumulates to a certain level. Drewnoski et al (2012) demonstrated that it took at least 29 days for the SRB to achieve peak rumen H 2 S production after abrupt exposure to diets containing a readily available sulfur source from Na 2 SO 4 . Maybe that is why it would present damage on animal performance when feeding high dietary sulfur for a long time in feeding practice.…”
Section: Methodsmentioning
confidence: 99%